The Influence of Brand Awareness and Brand Trust on Brand Loyalty of Halal Skincare Products: The Mediating Role of Brand Love - Suryani, Wan (ESENSI: Jurnal Manajemen Bisnis, 2025)
This study aims to analyse the effect of brand awareness and brand trust on brand loyalty in Wardah brand halal skincare products, with brand love as a mediating variable. Using an explanatory quantitative approach, data was collected from 219 Muslim female respondents in Medan City through a Likert scale questionnaire. The analysis was conducted using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with SmartPLS. The results showed that brand awareness and brand trust have a positive and significant effect on brand loyalty, both directly and indirectly through brand love. This finding indicates that consumer loyalty to halal skincare products is not only formed by brand recognition and trust, but also influenced by emotional attachment to the brand. This study provides a theoretical contribution by integrating cognitive and affective dimensions in shaping brand loyalty, and provides practical implications for marketing strategies for halal products that focus on young Muslim female consumers.